A report on the occurrence of accessory triradii in the subdigital area, and carpal triradii on the palm in Polish and Czech populations - Gąsiorowski, Adam; Hajn, Václav (Polskie Towarzystwo Antropologiczne, 2000)
The study analyses the occurrence of accessory triradii and carpal triradii on human palms in two populations. Accessory triradii were observed in Polish and Czech populations very rarely (triradius d' was most frequent). The occurrence of the abortive main line C(Y) was observed more often in the Polish population and it was statistically significant difference. A very high symmetry was stated between the occurrence of forms C(Y) and c(X) on right and left palms. A higher frequency of occurrence was stated in the case of carpal triradius t in the Polish population and of triradius t' in the Czech population. However, the differences are not statistically significant.
Keywords: dermatoglyphics; carpal triradii; accessory triradii